Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish - Luz, Thiarlen Marinho da; Guimarães, Abraão Tiago Batista; Matos, Stênio Gonçalves da Silva; de Souza, Sindoval Silva; Gomes, Alex Rodrigues; Rodrigues, Aline Sueli de Lima; Durigon, Edison Luiz; Charlie-Silva, Ives [UNESP]; Freitas, Ítalo Nascimento; Islam, Abu Reza Md. Towfiqul; Rahman, Md. Mostafizur; Silva, Abner Marcelino; et al. (Elsevier, 2023)
While the multifaceted social, economic, and public health impacts associated with the COVID-19 pandemic are known, little is known about its effects on non-target aquatic ecosystems and organisms. Thus, we aimed to evaluate the potential ecotoxicity of SARS-CoV-2 lysate protein (SARS.CoV2/SP02.2020.HIAE.Br) in adult zebrafish (Danio rerio) at predicted environmentally relevant concentrations (0.742 and 2.226 pg/L), by 30 days. Although our data did not show locomotor alterations or anxiety-like or/and anxiolytic-like behavior, we noticed that exposure to SARS-CoV-2 negatively affected habituation memory and social aggregation of animals in response to a potential aquatic predator (Geophagus brasiliensis). An increased frequency of erythrocyte nuclear abnormalities was also observed in animals exposed to SARS-CoV-2. Furthermore, our data suggest that such changes were associated with a redox imbalance [↑ROS (reactive oxygen species), ↑H2O2 (hydrogen peroxide), ↓SOD (superoxide dismutase), and ↓CAT (catalase)], cholinesterasic effect [↑AChE (acetylcholinesterase) activity], as well as the induction of an inflammatory immune response [↑NO (nitric oxide), ↑IFN-γ (interferon-gamma), and ↓IL-10 (interleukin-10)]. For some biomarkers, we noticed that the response of the animals to the treatments was not concentration-dependent. However, principal component analysis (PCA) and the “Integrated Biomarker Response” index (IBRv2) indicated a more prominent ecotoxicity of SARS-CoV-2 at 2.226 pg/L. Therefore, our study advances knowledge about the ecotoxicological potential of SARS-CoV-2 and reinforces the presumption that the COVID-19 pandemic has negative implications beyond its economic, social, and public health impacts.
Keywords: Biomarkers; Danio rerio; Ecotoxicity; Environmental toxicology; New coronavirus